The role of the different aspects of academic motivation and competitiveness in explaining self-handicapping - Šimek, Damjan (Psihološka obzorja (Ljubljana), 2010)
In the present research on self-handicapping, the goal was to examine the role of different types of academic motivation according to the level of self-determination. Since the existing research on self-handicapping has examined only the role of interpersonal competition, we also aimed to explore the role of different kinds of competition, i.e., the role of the reasons that motivate people to participate in competition, and the role of the reasons for the avoidance of competition. 748 high school students participated in the study. Regarding the role of academic motivation in self-handicapping the prevailing role of amotivation stood out. Intrinsic motivation predicted self-handicapping negatively, but extrinsic motivation proved to be a positive predictor. The factor structure of the Academic Motivation Scale only enabled differentiation of the reasons for education on the level of three basic types. With regard to the role of the different dimensions of competitiveness in self-handicapping, results show that those denoted by fear of failure and self-worth protection proved to be more characteristic of self-handicapping than those defined by a high valuation of the importance of quality of task accomplishment. Among others, our research suggests that by diverting students away from hypercompetitive values, functionality of self-handicapping can be decreased.
Keywords: learning; učenje; motivacija; motivation; tekmovalnost; samooviranje; srednješolci